Outcome of post‐prostatectomy stress urinary incontinence surgery in men with preoperative idiopathic detrusor overactivity - Nikita R. Bhatt; Simona Ippoliti; Arjun Nambiar; Cristian Ilie; Ruth Doherty; Lee Smith (BJUI Compass)
Abstract Background Urodynamic evidence of storage dysfunction such as detrusor overactivity (DO) and/or poor compliance are present in up to 30–40% of patients after Radical Prostatectomy (RP). However, the current optimal management of men with DO on preoperative urodynamics prior to male stress urinary incontinence (SUI) surgery is not known. Methods We performed a systematic search of the literature including articles on patients undergoing SUI surgery after prostatectomy with preoperative DO between January 2003 and May 2023 to ensure contemporaneous data was obtained. Results We identified 11 eligible publications with a total of 792 patients. On Urodynamics, 29% (n = 229) patients had DO prior to SUI surgery. Overall 69% patients had a successful outcome after SUI surgery while 26% (132/499) failed while 34% (32/95) patients who had proven DO preoperatively failed SUI surgery. The difference was not statistically significant. Considering the sub‐group analysis, the failure rate with preoperative DO was significantly higher in the sling group (43%) than in the AUS group (18%). The review was limited by the outcome heterogeneity, variability in study inclusion criteria, reporting and analysis and the quality of the available studies. Conclusions Within the limitations of the data, this review did not show a statistically significant higher failure rate of male incontinence surgery in patients with DO. Hence, patients with DO on preoperative urodynamics who are eligible for male SUI surgery should not be denied surgery but should be counselled appropriately of the risks and potential need for subsequent treatment, to manage expectations.